Răspuns :
x² + 20x + 91= x² + 20x + 100 - 9 = x² + 20x + 10² - 3² = (x + 10)² - 3² =
= (x+10 - 3)(x + 10 + 3) = (x + 7)(x + 13)
..
\\
Am putea izola o diferență de pătrate astfel:
x² + 20x + 91 = x² + 20x+140 - 49 = (x² - 49) +20x +140 =
=(x² - 7²) +20(x + 7) = (x - 7)(x + 7) + 20(x + 7) = (x + 7)(x - 7 + 20)=
=(x + 7)(x + 13)
\\
Am putea izola o diferență de pătrate astfel:
x² + 20x + 91 = x² + 20x+140 - 49 = (x² - 49) +20x +140 =
=(x² - 7²) +20(x + 7) = (x - 7)(x + 7) + 20(x + 7) = (x + 7)(x - 7 + 20)=
=(x + 7)(x + 13)
\\